ORGANIZATIONAL-FUNCTIONAL MECHANISMS OF CULTURAL ACTIVITY IN SOCIAL PROTECTION - Baxramova Nodira; Yusupova Rahima Kasimovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of cultural activity in the social protection system and its organizational-functional mechanisms. The social integration, rehabilitation, communicative and educational functions of cultural activity are highlighted, and its importance in working with segments of the population in need of social protection is revealed. The role of the state, civil society institutions and the neighborhood system in organizing cultural activity is also indicated, and priority areas for the development of the sector are considered.